A genre analysis on the roles of rhetorical structures and discourse markers in Malaysian newspaper reports - Hafizah, Hajimia (2020)
There are a number of issues related to the rhetorical structures of newspaper reports. From the ESP perspective, students of journalism courses still lack the knowledge of using appropriate rhetorical structures of newspaper reports. Understanding various forms, functions and positions of the linguistic structure of a genre is crucial to overcome the issues to achieve the communicative purposes embedded in the genre. However, there are limited studies on newspaper report’s structural linguistics patterns from the aspect of rhetorical structures (moves) and the use of discourse markers. Thus, there is a need to analyse how the rhetorical structures (moves) and the discourse markers are used in a newspaper report. Using the genre theory, this study analysed the frequency, patterns and the functional relations of moves and discourse markers in the corpus of online newspaper articles. The corpus consisted of ninety articles from the crime, politics and environmental news published in The Star newspaper. A corpus-based approach was used to code and calculate the frequency and patterns of the moves and discourse markers. The functions of the moves and the discourse markers were examined to see the relations within the moves. The data indicated that nine-move structures were identified with five optional moves and four obligatory moves. A hybrid and cyclical pattern emerged from the distributional patterns. Different grammatical word classes of discourse markers existed in the newspaper report. Based on the distributional patterns, the discourse markers occurred in the initial, middle and end of the sentences. Most of these discourse markers were found to serve a number of roles with the most occurrences of concession, evaluation, reason, and elaboration. The findings of this study can be useful for journalists, curriculum designers, translators, learners and instructors. Implication of the study revealed the importance of the rhetorical moves and DMs in specific genres for writers. Further analyses indicated the need for research of various patterns of the moves and DMs on the basis of large-scale genre research, analyse other sub-genres and comparison of newspaper reports with other countries in the future.